Third-generation Business Incubation Practices in Malaysian ICT Incubators - A Bridge Too Far? - Abdul Khalid, Fararishah; Gilbert, David; Huq, Afreen (North American Business Press, 2012)
Business incubation is an economic development tool that is widely used to stimulate the growth of small to medium sized enterprises (SMEs). The Malaysian government in line with the country’s aspirations to become a developed nation by the year 2020, has established its own incubation programs to catalyze the growth of ICT SMEs. This paper examines four constructs of the business incubation process: Selection Performance, Monitoring and Business Assistance Intensity, Resource Allocation and Professional Management Services. A total of 118 incubatees from ICT incubators in Malaysia responded to an online survey questionnaire. Principal component analysis and multinomial logistic regression analysis were used to determine the components of business incubation process and test their relationships with Business Incubation Performance. Results show that all four constructs and their respective components are significant predictors of Business Incubation Performance. The findings provide valuable information for policy makers, business incubator managers, and potential incubatees regarding better incubation management practices thus driving incubator development towards best practice, third generation incubators.